Can Farmer Multipliers Successfully Manage Net Tunnels? - International Potato Center (2014)
Farmer groups with designated leaders charged to maintain vine conservation (net) tunnels near their own homes on behalf of the group were best able to maintain the tunnel itself and vine quality during two years. Tunnels managed by youth groups or located near water distant from a member’s home and collectively managed by a group were least able.